Piloting the Climate Security Sensitiveness Scoring Tool (CSST). A case study assessing the climate security sensitiveness of Participatory Rangeland Management (PRM) in Baringo, Kenya - Sarzana, Carolina; Melgar, Adriana; Meddings, George; Läderach, Peter R.D.; Pacillo, Grazia (CGIAR FOCUS Climate Security, 2022)
Climate adaptation interventions, such as programs promoting climate-smart agricultural innovations, are proving effective in increasing farmer resilience as well as food and nutrition security (Mizik, 2021; Thornton et al., 2022). However, there is often little understanding of the potential positive and negative externalities that these programs can have (Smith et al., 2021), particularly in terms of peace and security. Maladaptation is the process whereby improperly built adaptation strategies can result in more vulnerability of other systems, sectors or social groups (Schipper, 2020; Barnett & O’Neill, 2010). It can create and sustain lock-ins, magnify inequity, marginalize people, and places vulnerable to climate-related risks, such as low-income households, people who reside in informal settlements, ethnic minorities, and Indigenous Peoples among others (IPCC, 2022). These are commonly recognized drivers of conflict which must be accounted for while designing programs to avoid creating or exacerbating conflicts. Acknowledging the interlinkages between climate action, natural resource use and peace and security is fundamental to integrate climate and conflict-sensitive programming interventions. Maladaptive climate initiatives neglecting those associations can foster power asymmetries, grievances, and competition for resources, especially in conflict-affected and fragile contexts (Moran et al., 2018; Krampe et al., 2021).